Increased stroke risk among patients with open-angle glaucoma: a 10-year follow-up cohort study. Issue 3 (20th July 2017) - Rim, Tyler Hyungtaek; Lee, Sang Yeop; Bae, Hyoung Won; Kim, Sung Soo; Kim, Chan Yun
Abstract : Background: Although several studies showed the association between stroke and open-angle glaucoma (OAG), there is still lack of longitudinal studies based on large populations. Therefore, in this study, we investigated the risk of stroke after OAG diagnosis over a 10-year follow-up period. Methods: We performed a retrospective nationwide propensity score-matched cohort study. OAG and comparison groups were selected from a large database from the Korean National Health Insurance Service, comprising 1 025 340 random subjects. The OAG group comprised patients with an initial diagnosis of OAG between January 2004 and December 2007 (n=1520), and the comparison group comprised randomly selected patients (five per glaucoma patient; n=7570). Each cohort was tracked until 2013 for stroke development. Cox proportional hazard regression analysis was performed to determine possible association Results: OAG was associated with increased stroke incidence (HR=1.20, 95% CI 1.03 to 1.40). Hypertension, diabetes mellitus, chronic renal failure, atrial fibrillation, hyperlipidaemia, increasing age and male gender also increased the incidences of stroke. Risk of stroke for patients with OAG was greater in the older age group (≥65 years, HR=1.23, 95% CI 1.02 to 1.47) than in the younger age group (<65 years, HR=1.12, 95% CI 0.86 to 1.46), and greater in males (HR=1.31, 95% CI 1.06 to 1.60) than in females (HR=1.10, 95% CI 0.88 to 1.38). Conclusions: Patients who were diagnosed with OAG were more likely to experience subsequent stroke than comparison group without OAG, and the risk was greater for older adults and males.